Pembuatan dan Pengujian Mesin Press Sampah Untuk Pembangkit Listrik Tenaga Sampah (PLTSA) Di Kampus UNSIKA - Kusuma Wahyu Wijaya; Marno; Iman Dirja (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The problem of waste will never be solved as long as people live on this earth, and during that time the problem of waste will be discussed from various points of view. One of the tools created to facilitate human industrial production is the printing press. This machine works by placing sheet metal with a mould (a pressing tool used to cut or form sheet metal into the desired shape) between the upper and lower moulds. This is the background for the author to apply, for example, to the manufacture of a waste compactor in a waste factory. For each sample, the aim of this research is to reach 5 kg per day and can exceed the research target as long as the energy is strong and there are still regular and irregular waste variables.